STRATEGI MANAJEMEN DALAM MEREKRUT CALON JAMAAH UMROH (STUDI KASUS PADA ALHIJAZ TOUR BANDAR LAMPUNG) - Habibah Nur Desi (Institut Agama Islam Negeri Metro, 2022)
Religious tourism travel shows an increasing trend from year to year, not to mention the Umrah trip which is also known as the “minor pilgrimage”. This increase makes travel agents vying to approach prospective pilgrims. Thus, this study intends to determine the management strategies used by travel agents, including human resource management (HR) and the marketing mix in recruiting prospective pilgrims. This research method is a case study on Alhijaz Tour Travel Bandar Lampung. The primary data sources (key informants) in this study were the head of the foundation, managers, staff, pilgrims and prospective Umrah pilgrims. Methods of data collection is done by interview, documentation, and observation. The data analysis technique used is pattern matching and explanation building. The results show that Alhijaz Tour Travel has implemented a HR development strategy through recruitment patterns, needs analysis, job analysis, salaries and bonuses, career advancement, and working according to job descriptions. Strategic planning is developed through long term and short term patterns. In addition, Alhijaz Tour Travel also implements a marketing mix consisting of products, prices, places and promotions designed in such a way as to attract the interest of prospective pilgrims.